Football marketing and its effect on economic boom - Masuod Homayounifar; Kamran Pahlavan Mosaveri; Elmira Shahriari (Atlantic Review of Economics, 2014)
Football sport marketing has been considered a tool, on economizing sports, producing the value added and an important solution for earning income through sports. The aim of this study was to investigate the role of football marketing in the country's economic boom, and the method of analytical survey was conducted using questionnaires. The study statistical society consisted of football experts, economists, management experts and football fans. The statistical sample was selected from a suitable classified sampling method in Tehran city. Multiple and linear regression analysis was used to analyze the data by SPSS and SAS software. The results show that football marketing has significant and positive effect on economic boom. In other words, football marketing components such as: the establishment of a central marketing system in football, brand advertising (internal and external), football stars are attracted by the club, attracting sponsors (internal and external), and to enhance the quality and quantity of the stadiums, has the effect positive on increasing the country's football industry.
Keywords: M31; M37; O40; 330; football; marketing; economic; boom; Iran